PENGARUH PERSEPSI HARGA, KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN: (Studi pada Konsumen Kopi Dari Hati Petrocafe, di Kabupaten Penukal Abab Lematang Ilir, Sumatera Selatan) - Ridho Vriya Pratama; Ravindra Safitra Hidayat (Jurnal Ilmiah Manajemen dan Akuntansi, 2024)
This research aims to examine the influence of price perceptions, product quality and service quality on purchasing decisions.  Sampling in this study used a purposive sampling technique with a total of 135 respondents.  Data was collected through a questionnaire with a Likert scale which was processed using Microsoft Excel 2019 software and SPSS version 26 software. The research method used was multiple linear regression.  The results of this research show that the variables of price perception, product quality and service quality have a positive and significant effect on purchasing decisions.  The results of the research are expected to provide information that perceptions of price, product quality and service quality can improve consumer purchasing decisions for Kopi Dari Hati Petrocafe.